Optimism Of Larry Crowne Reflected In Tom Hank's Larry Crowne Movie (2011): An Individual Psychological Approach - Susanti, Susi, Dr. Phil. Dewi Candraningrum, S.Pd., M. Ed, Drs. H. Abdillah Nugroho, M. Hum (2013)
This study is aimed to show Larry‟s character in Larry Crowne movie (2011) by using individual psychological approach. It is finish by establishing three objects: the first is analyzing the movie based on structural elements and the second is analyzing the movie based on the Individual Psychological approach. And the last is analyzing the movie based on the theory issue Optimism. This research is descriptive qualitative research. Type of the data of the study is text and image taken from two data sources: primary and secondary. The primary data source is the Larry Crowne Movie directed by Tom Hank release in 2011. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes three following conclusions. First, based on the structural analysis of each element, its shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography, sound, and editing are related to each other and form of unity. Second, based on the Individual Psychological analysis reflected in the character and characterization in Fictional finalism, inferiority feeling, striving superiority, social interest, style of life, Creative power all of this have meaningful goal in human‟s life. The last is based on the Theory Optimism are Dispositional Optimism, Unrealistic Optimism, Optimism as Attribution style, Comparative Optimism, Situational Optimism, Strategic Optimism, Realistic Optimism, Optimism Bias, all of the theory can be standard human‟s life.